The Utilization of Poly-37,40-diallyl-38,39,41,42,-tetrahydroxycalix[6]arenes Compound as Adsorbent for Heavy Metal Cations Cd(II), Cr(III) and Cu(II) - Susy Yunita Prabawati; Jumina Jumina; Sri Juari Santosa; Mustofa Mustofa (Jurnal Kimia Riset, 2020)
This research aims to examine the capability of poly-37,40-diallyl-38,39,41,42,-tetrahydroxy-calix[6]arenes as adsorbent for heavy metal cations such as Cd(II), Cr(III) and Cu(II). The adsorption process was carried out by batch method in the variation of acidity (pH), contact time and initial concentration of metal ions. The adsorption kinetics and adsorption isotherms were also studied. The results of this research showed that the amount of adsorbed metal increased with the increasing of the pH of metal solution. The amount of metal ions Cd(II) and Cr(III) adsorbed was optimum at pH 5, while for metal ion Cu(II) was optimum at pH 4. The optimum contact time for Cd(II), Cr(III) and Cu(II) was 60; 30; and 180 minutes, respectively. The study of adsorption kinetics showed that the adsorption of Cd (II), Cr (III) and Cu (II) metal ions using this adsorbent followed kinetics model of Ho. Isothermal studies showed that the adsorption of the three metal ions tends to follow the Langmuir isotherm. The adsorption capacities of Cd (II), Cr (III) and Cu (II) metal ions with poly-37,40-diallyl-38,39,41,42,-tetrahydroxycalix[6]arenes were 7.06; 14.72 and 38.45 µmol/g, respectively.